2017
DOI: 10.1111/all.13140
|View full text |Cite
|
Sign up to set email alerts
|

Differences in eosinophil molecular profiles between children and adults with eosinophilic esophagitis

Abstract: Children with EoE can be distinguished from healthy children based on the molecular patterns of their blood eosinophils. Age-related physiologic differences in eosinophil molecular patterns may partly explain the different blood eosinophil phenotypes in children vs adults with EoE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 37 publications
(84 reference statements)
1
23
0
Order By: Relevance
“…22,23 Analysis of protein expression patterns in gut biopsy samples from patients with celiac disease found a positive correlation between CLC/Gal-10 levels and tissue damage, and a recent study showed that higher levels of CLC/Gal-10 mRNA distinguished children with eosinophilic esophagitis from control children. 24,25 A recent report by Persson et al showed that human CLCs administered directly into mouse airways act as a type 2 adjuvant, mimicking many features of human asthma; the effects were readily reversible by CLC-dissolving anti-Gal-10 mAbs, suggesting a possible therapeutic approach. 26 Intriguingly, in addition to the considerable amounts present in eosinophils and basophils, CLC/Gal-10 is also expressed in human CD4 1 CD25 1 regulatory T cells, where it is necessary for the maintenance of immunosuppressive functions.…”
mentioning
confidence: 99%
“…22,23 Analysis of protein expression patterns in gut biopsy samples from patients with celiac disease found a positive correlation between CLC/Gal-10 levels and tissue damage, and a recent study showed that higher levels of CLC/Gal-10 mRNA distinguished children with eosinophilic esophagitis from control children. 24,25 A recent report by Persson et al showed that human CLCs administered directly into mouse airways act as a type 2 adjuvant, mimicking many features of human asthma; the effects were readily reversible by CLC-dissolving anti-Gal-10 mAbs, suggesting a possible therapeutic approach. 26 Intriguingly, in addition to the considerable amounts present in eosinophils and basophils, CLC/Gal-10 is also expressed in human CD4 1 CD25 1 regulatory T cells, where it is necessary for the maintenance of immunosuppressive functions.…”
mentioning
confidence: 99%
“…However, it is important to note that not all eosinophils are the same, even within the same disease and organ system. Eosinophils differ in their molecular pattern as observed by Lingblom et al when investigating differences in children and adults with eosinophilic esophagitis ( 123 ). Moreover, investigations in healthy individuals revealed age-dependent differences in levels of eosinophil markers.…”
Section: Known Mechanism Of Eosinophils With Potential Roles In Bp (Hmentioning
confidence: 85%
“…For instance, levels of CD44 increased with age, while levels of CD54, prostaglandin DP2 receptor (CRTH2), and galectin-10 decreased with age. In addition, they demonstrated that young healthy children express highest levels of galectin-10, CRTH2, and CD54 and that these diminish with age ( 123 ). Similarly, the gastrointestinal system hosts substantial number of eosinophils exhibiting differences to eosinophils in the lungs or blood.…”
Section: Known Mechanism Of Eosinophils With Potential Roles In Bp (Hmentioning
confidence: 99%
“…The use of advanced techniques (Roth et al ; Wilkerson et al ) to identify surface and secreted proteins in health and disease states in the horse would firstly improve the clinical utility of eosinophil counts, and secondly facilitate research as described below. What is the effect of age on equine eosinophil biology? Age‐related variation in eosinophil function is recognised in human subjects (Mathur et al ; Lingblom et al ). Age‐associated variation in eosinophils is evident in normal horses, response to pathogens and EADs, but molecular mechanisms are unknown.…”
Section: Discussionmentioning
confidence: 99%